Overtime Labor, Employment Frictions, and the New Keynesian Phillips Curve - Madeira, João (The Review of Economics and Statistics, 2014)
This paper presents a New Keynesian (NK) model that is extended to differentiate between straight time and overtime work. The model proposes that the New Keynesian Phillips curve (NKPC) should be estimated with marginal cost measured in terms of overtime labor; the resulting coefficient estimates are in accordance with theory and statistically significant for the hybrid NKPC (which allows for backward-looking price setters) but not for the purely forward-looking NKPC. In the hybrid model, backward-looking behavior is found to be predominant. The paper also shows that the incorporation of employment frictions (predetermined employment and convex adjustment costs) in NK models helps reconcile the frequent price changes found in the microdata with the degree of sluggishness in inflation adjustment to output changes at the macro level. © 2014 The President and Fellows of Harvard College and the Massachusetts Institute of Technology